Probing the self-assembly and stability of oligohistidine based rod-like micelles by aggregation induced luminescence. Issue 24 (14th March 2016) - Frisch, Hendrik; Spitzer, Daniel; Haase, Mathias; Basché, Thomas; Voskuhl, Jens; Besenius, Pol
Abstract : The synthesis and self-assembly of a new C 2 -symmetric oligohistidine amphiphile equipped with an aggregation induced emission luminophore is reported. Abstract : The synthesis and self-assembly of a new C 2 -symmetric oligohistidine amphiphile equipped with an aggregation induced emission luminophore is reported. We observe the formation of highly stable and ordered rod-like micelles in phosphate buffered saline, with a critical aggregation concentration below 200 nM. Aggregation induced emission of the luminophore confirms the high stability of the anisotropic assemblies in serum.